Efficient Swing Control Of An Overhead Crane With Simultaneous Payload Hoisting And External Disturbances - Liyana Ramli; Noor Hanis Izzuddin Mat Lazim; Z. Mohamed; M.O. Efe; H.I. Jaafar (Elsevier, 2024)
Mechanical Systems and Signal Processing Volume 135, 1 January 2020, 106326